2017
DOI: 10.1080/17512433.2018.1412827
|View full text |Cite
|
Sign up to set email alerts
|

Non-oncotic properties of albumin. A multidisciplinary vision about the implications for critically ill patients

Abstract: Effective resuscitation with human albumin solutions is achieved with less fluid than with crystalloid solutions. However, the role of albumin in today's critical care unit is also linked to its multiple pharmacological effects. Areas covered: The potential clinical benefits of albumin in select populations of critically ill patients like sepsis seem related to immunomodulatory and anti-inflammatory effects, antibiotic transportation and endothelial stabilization. Albumin transports many drugs used in critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 129 publications
(93 reference statements)
0
64
0
1
Order By: Relevance
“…It is interesting to note that, in contrast, disease‐associated deaths from 2 published outcome studies of IBD in dogs were considerably lower at 13% and 18%, suggesting that the PLE underlying disease mechanisms are not merely a more severe continuum of IBD spectrum pathophysiology. Perhaps, this is not unexpected when considering the functions of lymph fluid in immune defense, and the role of albumin in systemic immunomodulatory and anti‐inflammatory activities, antioxidant properties, and endothelial stabilization …”
Section: Lymphatic Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that, in contrast, disease‐associated deaths from 2 published outcome studies of IBD in dogs were considerably lower at 13% and 18%, suggesting that the PLE underlying disease mechanisms are not merely a more severe continuum of IBD spectrum pathophysiology. Perhaps, this is not unexpected when considering the functions of lymph fluid in immune defense, and the role of albumin in systemic immunomodulatory and anti‐inflammatory activities, antioxidant properties, and endothelial stabilization …”
Section: Lymphatic Structure and Functionmentioning
confidence: 99%
“…When TE is suspected, HS or purified canine albumin is preferable over plasma transfusion to avoid thrombus extension. The provision of parenteral nutrition via a central venous catheter is another means of increasing plasma oncotic pressure while providing nutritional support, with the unfortunate caveat of higher risks of sepsis, local infection/abscess, and thrombosis …”
Section: Management Of Plementioning
confidence: 99%
“…In fact, it has been recently demonstrated that an albumin level <3.5 g/dL was associated with worse outcome and coagulopathy [25][26]. In order to understand the pivotal role of albumin in SARS-CoV-2 infection, we should be aware that serum albumin possesses anti-oxidant and anti-in ammatory properties and behaves as an inverse acute phase reactant during acute systemic in ammation [27][28][29]. Furthermore, stressed and in amed cells increase the uptake of albumin from the circulation, thus highlighting a complex relationship between in ammation/infection and albumin level in the extracellular matrix [30][31].…”
Section: Several Studies Have Identi Ed a Close Correlation Between Hmentioning
confidence: 99%
“…Recent evidence and experts' consensus seem to favor the use of hypertonic albumin considering its effect on organ protection and edema correction [4]. 3) How to maintain the plasm albumin level at an optimal range by intravenous administration of albumin in selected time intervals [5]. So far, there have been a few clinical trials reported in the literature, targeting at the questions directly.…”
Section: Introductionmentioning
confidence: 99%